Optimization of silk fibroin coating during storage using response surface methodology and its effect on the physicochemical properties of Solanum ferox (S. ferox) - Hamzah, Muhammad Hazwan; Md Rahim, Anies Zulaikha; Maringgal, Bernard; Mohd Basri, Mohd Salahuddin; Ibrahim, Salis (Springer, 2022)
Silk fibroin coating was used in this study as an edible coating for Solanum ferox (S. ferox), tropical fruit from Borneo. The effect of different concentration coatings and dip time on fruit quality attributes during storage was evaluated via response surface methodology. The optimal parameters were 2% silk fibroin concentration and 2 min of dip time. The optimized data for silk fibroin-coated fruit, carboxymethylcellulose-coated fruit and uncoated fruit as a control were compared. The weight loss and firmness at day 11 for fruit coated with silk fibroin were 14.9% and 3.07 N, respectively, compared to 13.49% and 3.53 N for fruit coated with carboxymethylcellulose. Uncoated fruit revealed a weight loss was 28.11% and firmness was 4.3 N. On day 11, the fruit coated with silk fibroin had chemical properties of 3.6 and 4 for total soluble solids (TSS) and pH, respectively. The carboxymethylcellulose-coated fruit had a TSS of 4.2 and a pH of 3.3. The uncoated fruit had a TSS of 4.3 and a pH of 5.2. In comparison to uncoated fruits, the ripening process of fruits coated with silk fibroin was slowed. Silk fibroin is suggested to be an effective edible coating for preserving fruit quality and extending its shelf life.